Optimal Decision-Making on Hybrid Off-Grid Energy Systems for Rural and Remote Areas Electrification in the Northern Cameroon - null Yaouba; Ruben Zieba Falama; Felix Ngangoum Welaji; Marcel Hamda Soulouknga; Fabrice Kwefeu Mbakop; Abdouramani Dadjé (Journal of Electrical and Computer Engineering)
Hybrid renewable energy systems are effective solutions to the problem of lack of electricity in many localities around the world. In this paper, a comparative study of ten different options of standalone hybrid energy systems is done. These systems are used for household energy supply in rural and remote areas. The three regions of the northern Cameroon have been chosen as study sites. HOMER optimization Pro software has been performed for the optimal sizing of the proposed systems. The system reliability, the cost of energy, the renewable energy penetration, and the carbon dioxide emissions are the main comparative indexes considered. For an energy demand of 46418.100 kWh/year and a lifetime project of 25 years, the best optimal system configuration for the sites considered based on economic analysis is the PV/DG/battery system with a cost of energy of 0.378 $/kWh in Garoua, 0.359 $/kWh in Maroua, and 0.394 $/kWh in Ngaoundéré. When considering the environmental criteria, the PV/Battery and the PV/wind/Battery are the best options with 0 kgCO2 emissions per year and 100% renewable energy penetration. The renewable energy penetration of the PV/DG/Battery system is 95.6% in Garoua, 96.3% in Maroua, and 95.1% in Ngaoundéré. Thus, when taking into account both economic and environmental aspects, the PV/DG/Battery could appear as the best optimal system for rural and remote areas electrification in the northern part of Cameroon. The sensitivity analysis revealed that the studied systems are more attractive when increasing the project lifetime (up to 50 years, the COE is 0.375 $/kWh, 0.356 $/kWh, and 0.391 $/kWh, respectively, in Garoua, Maroua, and Ngaoundéré). However, the studied systems are more attractive when reducing the fuel price and the discount rate. When reducing the fuel price to up to 0.01 $/l, the COE is 0.359 $/kWh in Garoua, 0.342 $/kWh in Maroua, and 0.371 $/kWh in Ngaoundéré. When reducing the discount rate to up to 1%, the values of the COE are 0.253 $/kWh, 0.240 $/kWh, and 0.264 $/kWh, respectively, in Garoua, Maroua, and Ngaoundéré.